Factors Affecting The Performance Operational Assistance Budget Health Center at Palu City - Henni Mande; Guasmin; Burhanuddin; Nasrulhak Akkas; Iva Nuranifa (IECON: International Economics and Business Conference, 2025)
This study aims to analyze the influence of budget planning, budget implementation, and budget accountability on the performance of the health operational assistance budget at the Palu City Health Center. This study uses a quantitative method with a research sample of 42 employees. The data analysis technique used multiple linear regression. The results of the study show that the variables of budget planning, budget implementation, and budget accountability for the performance of the health operational assistance budget are partially  the variables of budget planning, budget implementation, and budget accountability for the performance of the health operational assistance budget. The correlation coefficient value (R) shows that the relationship between motivation, work environment, and compensation variables with employee performance is 96.8% (very strong) with a determinant coefficient value (Adjusted R-Square) of 0.933 means that the variables of budget performance can be explained by the variables of budget planning, budget implementation, and budget accountability of 93.3%.